The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1096/fj.201901327r
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of butyrate are inversely related to portal hypertension, endotoxemia, and systemic inflammation in patients with cirrhosis

Abstract: Short‐chain fatty acids (SCFAs) are gut microbiota‐derived products that participate in maintaining the gut barrier integrity and host's immune response. We hypothesize that reduced SCFA levels are associated with systemic inflammation, endotoxemia, and more severe hemodynamic alterations in cirrhosis. Patients with cirrhosis referred for a hepatic venous pressure gradient (HVPG) measurement (n = 62) or a transjugular intrahepatic portosystemic shunt placement (n = 12) were included. SCFAs were measured in por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 51 publications
2
79
1
Order By: Relevance
“…Accumulating studies show that hypertension is strongly associated with enteric dysbacteriosis, which is accompanying with reduction in butyrate-producing bacteria [92,[126][127][128]. Interestingly, circulating levels of butyrate are inversely related to portal hypertension [129], and butyrate could directly suppress Ang II-induced hypertension through inhibiting renal (pro)renin receptor (PRR)-mediated renin release [130]. However, the fundamental mechanisms underlying butyrate roles in regulating atherosclerosis and hypertension are not known.…”
Section: Butyrate and Butyrylationmentioning
confidence: 99%
“…Accumulating studies show that hypertension is strongly associated with enteric dysbacteriosis, which is accompanying with reduction in butyrate-producing bacteria [92,[126][127][128]. Interestingly, circulating levels of butyrate are inversely related to portal hypertension [129], and butyrate could directly suppress Ang II-induced hypertension through inhibiting renal (pro)renin receptor (PRR)-mediated renin release [130]. However, the fundamental mechanisms underlying butyrate roles in regulating atherosclerosis and hypertension are not known.…”
Section: Butyrate and Butyrylationmentioning
confidence: 99%
“…There is a further reduction of SCFAs in cirrhosis with HE. Butyrate has a negative correlation with inflammatory markers and serum endotoxin (Juanola et al, 2019). SCFAs bind the G-protein-coupled receptor 43 (GPR43) to promote the regression of inflammation (Maslowski et al, 2009).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…Acetic acid and propionic acid are metabolized and used in the liver and muscle. Juanola et al 25 . reported that short chain fatty acids (mainly butyric acid) are inversely correlated with the model for end‐stage liver disease score and were reduced in patients with a history of ascites, hepatic encephalopathy, or spontaneous bacterial peritonitis.…”
Section: Discussionmentioning
confidence: 99%